Refrigeration & air conditioning technology - Whitman, William C., 1930- (Clifton Park, N.Y. : Delmar Cengage Learning, 2013)
Equip yourself with the knowledge and skills to maintain and troubleshoot today's complex heating, air conditioning, and refrigeration systems with Refrigeration and Air Conditioning Technology, Seventh Edition. Now celebrating its 25th anniversary, this time-honored best seller provides the exceptional hands-on guidance, practical applications, latest technology and solid foundation you need to fully understand today's HVAC/R service and repair, its environmental challenges, and their solutions. Focused on sustainable technology in today's HVAC/R industry with an emphasis on new technologies and the latest advancements in the industry, the 7th edition has been updated to include more on green awareness, LEED accreditation and building performances with two new chapters on energy audits and heat gains and losses. This edition covers the all-important soft skills and customer relation issues that impact customer satisfaction and employment success. - Back cover.
Includes index.
Keywords: Refrigeration and refrigerating machinery; Air conditioning